Pelatihan Karya Tulis Ilmiah Sebagai Sarana Pengembangan Diri Siswa SMA - Prayogo, M. Ari; Rahmadani, Agung; Nuryadin, Atin; Palapa, Kaleb Gideon (Forum Kerjasama Pendidikan Tinggi, 2024)
Scientific writing training is an important means of student self-development, especially in terms of writing skills and critical thinking skills. This community service activity aims to provide scientific writing training to students of State Senior High School 1 Sangasanga. This training was held for two days, Wednesday and Thursday, September 25-26, 2024 at State Senior High School 1 Sangasanga starting at 08.30 WITA until finished. The training participants were 50 students from grade eleven (XI). The methods used in this training activity include providing materials, intensive guidance, and direct practice in compiling scientific papers. The results of this training showed a significant increase in students' abilities in compiling scientific papers systematically, critically, and based on facts obtained in the field. In addition, this training also motivated students to be more courageous in conveying creative and solution-oriented ideas. Thus, this training makes a positive contribution to improving students' academic quality. The results obtained after the end of this training were to provide input to participants, namely students, in writing scientific papers by training students' writing and critical thinking skills, as well as encouraging creative and innovative attitudes.